Cyclooxygenase-1 deletion in 5 × FAD mice protects against microglia-induced neuroinflammation and mitigates cognitive impairment - Jie Wang; Hong Ni; Yu Wang; Luyao Wei; Hanqing Ding; Zhongzhao Guo; Hao Pan; Ying Yu; Jia Luo; Weidong Pan; Deheng Wang; Zun-Ji Ke (Translational Neurodegeneration)
Abstract Background Alzheimer's disease (AD) is a neurodegenerative disease with major symptoms including memory and learning deficits. Neuroinflammation associated with reactive microglia promotes AD progression. These reactive microglia secrete prostaglandins, which are synthesized through the enzymatic activity of cyclooxygenase (COX)-1 and COX-2. Here, we aimed to elucidate the specific mechanisms of COX1 in AD pathogenesis and its interactions with neuroinflammatory processes. Methods We conducted backcrossing between COX-1 knockout (KO) and 5 × FAD mice to evaluate the effect of COX-1 deficiency on neuroinflammation. In addition, single-cell sequencing and microarray datasets from public databases and ingenuity pathway analysis in vitro were employed to explore gene expression profiles in the brains of AD mice. Results We identified a significant upregulation of COX-1 in 5 × FAD mice, with expression specifically localized to microglia in an age-dependent manner. Additionally, COX-1 KO alleviated neuroinflammation and accumulation of Aβ plaques, subsequently improving cognitive behavior in 5 × FAD mice. Moreover, microglia exhibited an amoeboid morphology in 5 × FAD mice, whereas in age-matched 5 × FAD/COX-1 KO mice, microglia had a ramified appearance. Additionally, our study demonstrated a pharmacological approach that inhibits the prostaglandin E2 (PGE2)/EP2 receptors via inhibition of the cAMP-PKA-NFκB-p65 pathway and NLRP3 inflammasome activation, producing similar beneficial effects as observed in COX-1 KO mice. Conclusion Our findings indicate that targeting the COX-1/PGE2/EP2 signaling pathway may alleviate neuroinflammation and impede AD progression. Moreover, the EP2 receptor presents a promising pharmacological target for mitigating the pathological effects associated with COX-1 activity in AD patients.